Comparison Between Conventional PID Controller and Neural Network PID Controller Based on DC Motor Speed Control - Mani Nepal, Subhamyu; Prasad Sapkota, Madan; Shrestha, Nischal; Karki, Sunil; Raj Dhungana, Manoj (KEC Journal of Science and Engineering, 2024)
DC motor is a multivariable, strong coupling and nonlinear controlled system, and is difficult to setting up the accurate mathematical model. So, it cannot achieve good control effect using traditional PID control method. To tackle this problem ANN based PID controller is proposed in this paper. The objective here is to compare the response of DC motor controlled by two different PID controllers.